Unveiling the Impact of Entrepreneurial, Organizational Learning, Innovation, and Customer Orientations on Innovation Performance: A Conceptual Framework - Muhammad Dharma Tuah Putra Nasution; Ramadhan Harahap; Irawan; Aulia Ramadhan Tanjung (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores the conceptual framework for understanding how entrepreneurial orientation, organizational learning orientation, innovation orientation, and customer orientation potentially impact innovation performance. Addressing the need for a comprehensive theoretical model, this research aims to clarify the roles of these orientations in fostering innovation within organizations. The study employs a conceptual approach, integrating existing literature to propose a model that outlines the relationships between these orientations and their expected effects on innovation performance. The conceptual framework suggests that entrepreneurial orientation drives innovation performance by creating a proactive and risk-taking environment. Organizational learning orientation is posited to enhance innovation performance through the continuous acquisition and application of knowledge. Innovation orientation is proposed to support innovation performance by emphasizing the development of new ideas and processes. Additionally, customer orientation is expected to improve innovation performance by aligning innovations with customer needs and preferences. This framework offers valuable insights for future empirical research and provides a foundation for understanding how these orientations can be effectively managed to boost innovation. Future studies are encouraged to test this model empirically to validate and refine the proposed relationships.